KEPEMIMPINAN KEPALA SEKOLAH BERBASIS KECERDASAN EMOSIONAL DAN MOTIVASI BELAJAR SISWA DI SMK NEGERI DISTRIK ABEPURA KOTA JAYAPURA PROVINSI PAPUA - Tatangin, Sumirna Paulina; Partino, Partino; Mataputun, Yulius (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
This research aims to analyze the impact of principal’s emotional-based intelligence leadership and students’ learning motivation in vocational schools in District Abepura Jayapura city of Papua Province. The study employed associative quantitative method. The subjects of the research were students of vocational schools in District Abepura, City of Jayapura, Papua Province with the population of 3.529 students and the sample of 97 students. The data for the research were mainly gathered from valid and reliable questionnaire, in depth-interview and also from related documentations. Pre-requisite test of data analysis included normality tets and linearity test. Data collected on the study were analysed using simple regression analysis through Statistical Package for Social Sciences (SPSS) version 23 software for windows. The result of the study indicates that principal’s emotional-based intelligence leadership held a positive and significant impact on students’ learning motivation in in vocational schools in District Abepura, City of Jayapura, Papua Province. The result of the study also demonstrates that there were significant relationship between principal’s emotional-based intelligence leadership and students’ learning motivation at significant level of 0,000 < 0,05 and the impact score of 66,8 % which shows positive value. This means that the higher the rate of principal’s emotional-based intelligence leadership, the better the students’ learning motivation. The finding of the study is expected to be used as a reference for educational stakeholders or teachers especially for the future education leaders in term of motivating students to learn better.Keywords: principal’s leadership; emotional intelligence; students’ learning motivation